Serum Magnesium Level is Associated with Excerbation Of Bronchail Asthma - Saeed, Muhammad Shahid; Shahid, Adeela; Jawed, Samia; Akram, Muhammad; Qureshi, Irshad Hussain (Annals of King Edward Medical University, 2019)
Bronchialasthma is one of the most common respiratory disorder with increasing prevalence among children and adults. During ionic study of disease Mg++ was found to be associated with exacerbation as well as treatment of the disease. Magnesium causes inhibition of smooth muscle contraction by competing with ca++, histamine release from mast cells by stabilizing outer membrane and acetylcholine release from cholinergic nerve terminals. All these processes results in relaxation of smooth muscles of bronchi which ultimately relieves the symptoms of asthma. Low magnesium level has been associated with asthma Objective :To determine the serum magnesium (Mg) concentration in asthmatics in acute attack, stable stage of asthma and its comparison with healthy individuals. Material and methods: 110 Subjects were enrolled in the study after their written consent, Among them 60 patients diagnosed as asthma(study group), 30 subjects with chronic stable asthma, 30 subjects with acute severe attack of asthma and 50 normal individuals as a control group.. Results: There was a significant decrease in Serum Mg levels instudy group as compared to control group. It was further observed that there is decrease in serum Mg++in asthmatic patients during acute attack of asthma as compared with stable stage of asthma. Moreover a positive correlation between serum Mg levels and lung function test especially FEV1 and FEV1/FVC ratio was observed in the present study. Conclusion: There is a strong relationship between asthma and serum magnesium level. It was further concluded that in asthmatics there is further decrease in serum Mg in acute exacerbation of the disease as compared to chronic stable asthma.